Loss-of-Function GRHL3 Variants Detected in African Patients with Isolated Cleft Palate. (January 2018) - Eshete, M.A.; Liu, H.; Li, M.; Adeyemo, W.L.; Gowans, L.J.J; Mossey, P.A.; Busch, T.; Deressa, W.; Donkor, P.; Olaitan, P.B.; Aregbesola, B.S.; Braimah, R.O.; et al.
In contrast to the progress that has been made toward understanding the genetic etiology of cleft lip with or without cleft palate, relatively little is known about the genetic etiology for cleft palate only (CPO). A common coding variant of grainyhead like transcription factor 3 ( GRHL3 ) was recently shown to be associated with risk for CPO in Europeans. Mutations in this gene were also reported in families with Van der Woude syndrome. To identify rare mutations in GRHL3 that might explain the missing heritability for CPO, we sequenced GRHL3 in cases of CPO from Africa. We recruited participants from Ghana, Ethiopia, and Nigeria. This cohort included case-parent trios, cases and other family members, as well as controls. We sequenced exons of this gene in DNA from a total of 134 nonsyndromic cases. When possible, we sequenced them in parents to identify de novo mutations. Five novel mutations were identified: 2 missense (c.497C>A; p.Pro166His and c.1229A>G; p.Asp410Gly), 1 splice site (c.1282A>C p.Ser428Arg), 1 frameshift (c.470delC; p.Gly158Alafster55), and 1 nonsense (c.1677C>A; p.Tyr559Ter). These mutations were absent from 270 sequenced controls and from all public exome and whole genome databases, including the 1000 Genomes database (which includes data from Africa). However, 4 of the 5 mutations were present in unaffected mothers, indicating that their penetrance is incomplete. Interestingly, 1 mutation damaged a predicted sumoylation site, and another disrupted a predicted CK1 phosphorylation site. Overexpression assays in zebrafish and reporter assays in vitro indicated that 4 variants were functionally null or hypomorphic, while 1 was dominant negative. This study provides evidence that, as in Caucasian populations, mutations in GRHL3 contribute to the risk of nonsyndromic CPO in the African population.